A study of children’s environmental awareness and discovery of hidden geographies based on the award-winning maps from the Asahikawa environmental map contest - Hyunjin KIM; Barbara Muhič (European Journal of Geography)
I this paper, we explored children’s environmental awareness and their discovering of hidden geographies. We employed a secondary data analysis using the 2018 and 2019 award-winning maps from the Asahikawa Environmental Map Contest, and an earlier study on the 2009 award-winning maps. Recently, most of the maps submitted to the contest have explored the cultural environment, whereas the number of maps related to the natural environment and environmental problems have decreased in comparison with the contest 10 years ago. This indicates that the natural environment is not so familiar to children because many of them live in urban areas. The maps showed children’s considerable scientific skills. Some children demonstrated an outstanding ability to map hidden geographies discovered through vivid sensory experience.